Characteristics of Correctly Identified Pediatric Obesity and Overweight Status and Management in an Academic General Pediatric Clinic. (September 2018) - Morais, Ana; Kelly, Joseph; Bost, James E.; Vaidya, Susma Shanti
This study identified and characterized the rates of documentation and guideline-based management of overweight and obese children within an academic pediatric clinic through a retrospective electronic medical record review of 7422 well-child visits in 2016. Diagnosis and treatment were analyzed by patient's weight diagnosis, sex, age, and provider training level. The percentages of correctly identified severely obese (90.2%), obese (77.0%), and overweight (42.0%) children were much higher than in previous retrospective chart reviews; however, less than 30% of children were referred for more intensive weight management to a dietitian or pediatric obesity weight management program. Increased provider training level was associated with a lower adherence to pediatric obesity guidelines. Strategic modifications to electronic medical records that automatically offer body mass index–associated weight diagnoses with a link to treatment pathways and resources are needed to facilitate improved compliance with current pediatric obesity guidelines in the primary care setting.